Early institutional experience using the TracStar Large Distal Platform in endovascular flow diversion. Issue 3 (June 2022) - Bageac, Devin V; Gershon, Blake S; Shigematsu, Tomoyoshi; Majidi, Shahram; De Leacy, Reade A
Introduction: The delivery of flow-diverting stents (FDS) necessitates a degree of catheter support beyond that required for endovascular coiling. The TracStar Large Distal Platform (LDP) is a novel 0.088″ platform intended for navigation into the intracranial internal carotid artery (ICA). We present an early institutional experience using the TracStar LDP in 44 cases of endovascular aneurysm embolization using FDS. Methods: Inclusion criteria for this single-center retrospective review encompassed all patients >18 years of age who were treated for intracranial aneurysms. Procedural success was defined as successful stent deployment using the TracStar LDP. Other outcomes included periprocedural complications, use of an intermediate catheter, length of stay, and discharge disposition. Results: The TracStar LDP was utilized in 44 consecutive FDS cases in 42 patients. Cavernous segment aneurysms constituted the majority of cases (12/42; 28.6%), followed by posterior communicating artery (8/42; 19.0%) and supraclinoid aneurysms (8/42; 19.0%). Successful FDS deployment was achieved in 43/44 cases. The LDP achieved stable positioning within the ascending cavernous ICA in 63.6% of cases. A biaxial system was utilized in 54.5% of cases. There was one complication potentially related to use of the TracStar LDP, which was an asymptomatic ICA vessel dissection managed conservatively. Conclusions: The TracStar LDP is safe and effective during use in the endovascular treatment of intracranial aneurysms with a FDS. Access to the ascending portion of the cavernous ICA was regularly achieved, and the platform allowed for both biaxial and triaxial configurations.